Desenvolvimento de métodos analíticos alternativos para microcistinas através da derivatização com probes ópticos - Oliveira, Andre Filipe Rodrigues de [UNIFESP] (2016)
The cyanobacteria inhabit different ecosystems and have substantial economic and ecological importance. However, they are a matter of concern when there is a massive growth of these organisms. Some secondary metabolites of these bacteria are toxic, named as cyanotoxins. Microcystins (MC) are the most prevalent class of cyanotoxins and some of its variants have shown high toxicity, mainly to the liver. The regulatory concentration limit of these toxins in water is 1 µg/L. Therefore, the microcystins monitoring requires the development of selective and sensitive methods. This study intends to explore the molecular derivatization as a key-tool to develop new analytical approaches of cyanotoxins. The project aims the synthesis of an optical probe to be added to the mycrocistin?s Mdha portion and the preparation of internal standards to be employed in analytical routines. Initially, MC were extracted from Billings Reservoir samples and the principal variants were identified. It was determined the MC proportion from February 2013 to July 2014 and correlated to the cyanobacteria composition in the same period. The statistical analysis highlighted a solid dependence between the production of MC-LR and the dominance of Planktothrix isothrix species, an unprecedented behavior until then. In order to improve the sensitivity of LC-MS methods involving ESI, we observed the improvement of microcystins ionization when acetic acid 10 mmol/L was used as additive in the mobile phase for LC-MS analysis. Microcystins esterification procedure was established and there were prepared the internal standards (IS). However, part of IS-monomethyl ester and all IS-dimethyl ester prepared have failed to derivatization essays with 2-mercaptoethanol and were not used for the proposed analytical development. The optical probe was synthesized and it was efficient as Michael's nucleophile in experiments with analogous molecules to the MDHA portion of MC. The probe showed maximum absorption at 241 nm and could increase the sensitivity of MC in optical detectors. Despite the low stability and solubility in aqueous media, the probe may be considered an initial platform that can be modified to lead to molecular probes with greater absorption and solubility.